2001
DOI: 10.1021/nl015528w
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Metal Nanoparticles in Photopolymerized Organic Conducting Polymers:  A Mechanistic Insight

Abstract: Electrically conducting polymers were prepared through a systematic photopolymerization of polypyrrole with the incorporation of Group 1B metal particles. The structural and morphological properties of incorporated metal nanoparticles were examined with respect to the role of the metals ions, nature of substrates, exposure time, and monomer counterion ratios. Elemental analysis confirmed the identities of the particles with sizes on the order of hundreds of nanometers in diameter. A mechanism is proposed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(77 citation statements)
references
References 13 publications
1
76
0
Order By: Relevance
“…22 Recent studies on photopolymerization of poly(pyrrole) in the presence of AgNO 3 as an electron acceptor and UV radiation have shown interesting results for the incorporation of metal nanoparticles into poly(pyrrole). 23,24 It has been suggested that this would be an appropriate route to prepare humidity sensors by coating polyester-based substrate with poly(pyrrole)/TiO 2 composites and studying its effect on the electrical and humidity sensing properties. 25,26 Previously, there were reports on the multiphotonsensitized polymerization of pyrrole, self-sensitized photopolymerization of pyrrole and photopolymerization of pyrrole using ruthenium complexes, cobalt complexes, and copper complexes as electron acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…22 Recent studies on photopolymerization of poly(pyrrole) in the presence of AgNO 3 as an electron acceptor and UV radiation have shown interesting results for the incorporation of metal nanoparticles into poly(pyrrole). 23,24 It has been suggested that this would be an appropriate route to prepare humidity sensors by coating polyester-based substrate with poly(pyrrole)/TiO 2 composites and studying its effect on the electrical and humidity sensing properties. 25,26 Previously, there were reports on the multiphotonsensitized polymerization of pyrrole, self-sensitized photopolymerization of pyrrole and photopolymerization of pyrrole using ruthenium complexes, cobalt complexes, and copper complexes as electron acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…One-pot synthesis approaches have also been developed, involving sonication [23,26], and UV- [15,28] or g-irradiation [27,32,41]. It was found that sonication and g-irradiation resulted in acceleration of the nanocomposite formation by inducing radical formation (i.e.…”
Section: Oxidative Polymerization Combined With Metal-ion Reduction (mentioning
confidence: 99%
“…For instance, in the case of Ag-PANI-PSS and Ag-PDMA-PSS nanocomposites, an improved thermal stability has been established [40]. Concerning the electrical conductivity, there are differing data showing increased [15,23,27,43] or preserved [20,40] conductivity of the composites in comparison with the corresponding pristine polymers, synthesized under identical conditions. In general, the problem with the influence of the metal NPs on the conductivity of the nanocomposite material is not easily handled.…”
Section: Oxidative Polymerization Combined With Metal-ion Reduction (mentioning
confidence: 99%
“…Multifunctional nanomaterial-incorporated conjugated polymer hybrid materials synthesized using various techniques, such as sol-gel synthesis, 1,2 electrochemical deposition, 3,4 and photochemical deposition, 5 have gained considerable research interest over the years. These materials in the form of colloids, films, and bulk have superior electro-catalytic activity 6,7 and applications in memory devices 8 and electrochemical super capacitors 9 over pure polymeric materials.…”
Section: Introductionmentioning
confidence: 99%